Impact of land management on soil macrofauna in the Eastern plains of Colombia - Decaëns, Thibaud; Lavelle, Patrick M.; Jiménez Jaén, J.J.; Escobar, G.; Rippstein, G; Schneidmadl, J; Sanz Scovino, José Ignacio; Hoyos, P.; Thomas, Richard J. (International Center for Tropical Agriculture, 2001)
The effects of different types of land management on the soil macroinvertebrate communities on acid soil savannas of Colombia have been assessed using the Tropical Soil Biology and Fertility Program (TSBF) methodology. Invertebrates were identified among broad taxonomic units, TU (Orders or Families), counted and grouped in larger units, i.e., earthworms, termites, ants, beetles, spiders, miriapods, and "other invertebrates". Both the gallery forest and the savanna had the highest taxonomic richness and population density (average 4293 and 2830 individuals/m2, respectively) with a medium biomass (13.6 and 15.3 g/m2). Termites (47%) and earthworms (31%) were the major components of biomass. Fire had a spectacular short-term effect on macrofauna. After 6 months, the soil fauna had regenerated: biomass and density were not significantly different from values recorded in the initial savanna and taxonomic richness increased to 20 TU. Macroinvertebrate communities of improved pastures were characterized by a high biomass and taxonomic richness and a medium population density. Pastures of associations of African grasses and forage legumes, had greatest earthworm biomass (22.9 to 51.1 g/m2), i.e., 4 to 10 times greater than that of the native savanna. Earthworm populations under pastures were composed of native species, with a large macrofaunal diversity (26 to 32 TU represented). Annual high input cropping systems (rice and cassava) had the lowest biomass 3.2-4.3 g/m2 and density 429-592 individuals/m2 and a low taxonomic richness, i.e., 18 TU. Macroinvertebrate communities of the well drained savannas of Colombia are very sensitive to environmental changes associated with agricultural intensification. The results obtained in these studies suggests various alternatives to conserve and stimulate the activities of soil macrofauna.